USING THE DIGITAL MODULE RAINBOW BOOK AS A SUPPORTING MEDIA FOR LEARNING MATHEMATICS IN IMPROVING THE UNDERSTANDING OF PRIMARY STUDENTS - Usmaedi Usmaedi; Putri Yuniar Fatmawati; Indhira Asih Vivi Yandari; Aan Subhan Pamungkas (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
This research is motivated by the lack of available mathematics teaching materials that are attractive and in accordance with the characteristics of primary school students. In addition, students' mathematical understanding is still low regarding the Geometry material. Based on these problems, the purpose of this research is to develop rainbow book teaching materials and to analyze the impact of using these teaching materials on mathematical understanding of students. This research is a development research using the 4D model, namely define, design, develop and disseminate. At the disseminate stage, an analysis of the impact of using teaching materials on student understanding is carried out. The instruments used were questionnaires and tests, questionnaires were used to assess the appropriateness of teaching materials both in terms of content and media. While the test is used to see students' mathematical understanding. Based on the results of the development, it was found that the rainbow book teaching material was feasible based on the content and media expert's assessment. The assessment of the two experts shows that the rainbow book can be used as teaching material in geometry materials for primary school students. In addition, based on the results of user responses, students stated that students showed good responses to learning using the rainbow book. The results of the comprehension test showed that the remainder after learning to use the rainbow book obtained an understanding score of 83.75 with a very good achievement category. Keywords: Teaching Materials, Rainbow Book, Student Understandig